Reduced False Memory in the Second Language of Turkish-English Bilinguals - Sıtkı, Merve; Ikier, Simay; ŞENER, NİLÜFER (Routledge Journals, Taylor & Francis Ltd., 2024)
In the Deese-Roediger-McDermott (DRM) paradigm, studying a list of semantically related words leads to false memory for the critical non-studied word that is related to all the words in the study list. Previous studies questioning whether bilinguals are more prone to false memory in their first language (L1) or second language (L2) in the DRM paradigm revealed mixed results. The present study investigated the same question with Turkish-English bilinguals. The revised hierarchical model proposes that the link between the lexicon and the semantic system is weaker in L2 than in L1, suggesting that false memory in the DRM paradigm that relies on semantic relatedness would be higher in L1 than in L2. Furthermore, previous studies showed that L2 is more resistant to errors in decision-making when the two languages are dissimilar, but not when they are similar, and Turkish and English are historically distant and typologically dissimilar languages. We tested Turkish-English bilingual participants whose L1 is Turkish with Turkish and English DRM word lists that had similar prior norms for generating false recognition. In the recognition test, some of the studied items and the critical non-studied items were presented and participants identified the studied items. False recognition for the critical non-studied items was lower and correct recognition for studied items was higher in L2 than in L1. The results suggest that L2 is more resistant to false memory due to its weaker lexicon and semantic system associations, at least when the two languages spoken by the bilingual are dissimilar.
Keywords: Bilingualism; DRM Paradigm; False Memory; Foreign Language Effect; Recognition Memory